Pengenalan Profesi Arsitek dan Perencana Kota melalui Kelas Hibrid Interaktif pada Masa Pandemi Covid-19 bagi Siswa SD di Banda Aceh - Agustina, Sylvia; Edytia, Muhammad Heru Arie; Zahrah, Aghnia; Burhan, Issana Meria; Harahap, Sri Anggina (PESARE: Jurnal Pengabdian Sains dan Rekayasa, 2024)
This article reports on the design and implementation of thematic extracurricular activities for primary school students regarding the introduction of two professions : architect and urban planner. The program was carried out during the pandemic with all the limitations for direct physical interaction. This report elaborated methods for combining materials and ways to manage interactions in such situation. The combination of materials is expected to provide an introduction to the professions and introduce knowledge about the field in an interesting and age-appropriate way for children. It also act as a proxy to reach parents and schools with architectural design and urban planning issues. Implementation that combines offline and online methods is an alternative model for implementing other activities both during the pandemic and in normal situations. The results of the activity show that students and parents were very interested and actively involved. The main obstacle faced and worth anticipating in implementing similar activities is the level of familiarity with online interactions (with was new at the time) and finding mechanisms for activities to develop scientific interests at an early age, not incidentally but on a regular basis.